Extending the design space of kinematics in electroactive shape memory polymers - Lai, Samson Iskandar (Nanyang Technological University, 2024)
This thesis presents advancements in the processing of electroactive shape memory polymers to enable new deployment modes for use as alternative construction material for deployable structures. Deployable structures are devices designed to transition from packaged forms for compact transportation, to functional forms for diverse applications such as space structures, emergency shelters, medical devices, and automotive safety systems. Traditional deployment relies on electromechanical systems, favored for their reliability and well-established design principles. These systems, however, often suffer from drawbacks including weight, volume, and complex assembly that can lead to increased potential for failure. Recently, the idea of shape memory polymer (SMPs) has emerged as a promising deployment mechanism. SMPs boasts advantages like their light weight, low cost, high-strain allowing for compact stowage and the ability to be programmed to remember and return to a predefined shape upon stimuli exposure. To remove the need for external heaters, SMPs can also be composited with conductive fillers into electroactive shape memory polymer composites (eSMPCs). These eSMPCs can self-stimulate and self-deploy through internal Joule-heating, driven by a small battery. Their electrical properties can also be tuned via various compositing options due to the wide range of nanofiller candidates. However, eSMPCs are limited in terms of their kinematics and deployment motions. Therefore, this thesis focuses on enhancing the deployment motions in eSMPCs as well as their electrical functionality through exploring new processing methods. Most existing eSMPCs feature stimulated recovery motions only in cantilevers, exhibiting bending or local folding at discrete hinges. However, other forms of shape-change behaviors, such as helixing/ twisting/ multiple bending in cantilevers or topographic change in sheets into curvilinear shapes have been largely unexplored. A key challenge to achieve design of shape-change behavior in eSMPCs requires being able to control the shape at which eSMPCs’ precursors were initially cured at. This requirement arises simply because the deployed shape by a thermoset-based eSMPCs is designated by the shape at which polymer precursors were crosslinked at, and the subsequent shape-change pathway is simply the returning of the temporary shape back to the as-fabricated shape. Therefore, the lack of shape-change modes is also caused by the limited design space of producible geometries with existing processing methods. Another factor contributing to limited shape-change modes problem in eSMPCs arises from the contradiction that shape-change modes are coupled with stretching strains, yet large stretching strains are detrimental to eSMPCs’ conductivity. In this thesis, new processing methods were developed in the aim of achieving eSMPC with deformable conductivity based on three-dimensional graphene foam (3DC) to retain excellent conductivity and EM-reflectivity, whilst also accessing new classes of geometry and shape-transformation modes. To allow deployment beyond simple bending/folding in cantilevers and improve upon the moderate conductivities in most eSMPCs (which are percolation-based), a new two-stage sequential cure-and-foam technique was developed to fabricate eSMPC with porous three-dimensional graphene (3DC) monolith. The new method resolved the difficulty in shaping fragile 3DC, and thus, various complex shape transforms (curved, helical, and wavy) can be intuitively designed via direct sculpting. The method is also compatible with kirigami techniques for the design of hierarchical and combinatorial shape-change structures. The embedded 3DC not only serves as an intrinsic heater but, during synthesis, its cell walls also act as a confinement framework for architecting porosity within 3DC-eSMPCs, which can be actuated with low-voltage (7.5 V, <2 W). A second identified gap is that existing eSMPCs are unable to deploy into curvilinear shapes nor able to be prescribed with spatially-differential curvature profile. Two main issues were identified : Existing eSMPCs lack a stretchable joule-heater material as well as lack a method to prescribe deployment cues which spatially-grades stretching and folding, both preventing existing eSMPCs from electroactively deploying into curvilinear shapes. In addressing these issues, we report a new processing method for electroactive shape memory polymer composites (eSMPC) which can be tailored with spatially-differential curvature during subsequent deployment --- a capability not yet feasible by past eSMPCs or their processing methodology, to form bent or curvilinear shapes. By overcoming these issues, we demonstrate deployment of eSMPC into shapes that would be extremely challenging to design for and deploy into if using methods in existing studies. Furthermore, the resulting 3DC-eSMPC exhibits highly-efficient self Joule-heating (<10 V) and high-frequency electromagnetic functionality (S11 of -1 dB for 28-33 GHz). With the kirigami-modification, we were also able to achieve a type of electromagnetic-functional active kirigami, that presents a new way to exploit deployment into “designer” curvilinear shapes and material’s electromagnetic functionality to manipulate radiation patterns. This work marks a significant stride for functional eSMPCs, which deploy not just for aesthetics’ sake but used as form-functional deployable structures. One particular form-functional structure of interest that has been flirted with eSMPCs have been deployable reflectors. The design of deployable antennas has enjoyed a rich history of eSMPCs research but due to the large strains involved during packaging, incumbent eSMPCs have proved too inextensible when reflector shell has to be packaged compactly. With the recent surge in privatization of space technologies and Satellite-based services and applications, a relook at the design approach of eSMPCs-based deployable antenna reflectors with suitable folding concept is timely. The folding problem is a highly complex one that requires concurrent consideration of eSMPC fabrication, material’s electromagnetic reflectivity, planning of deployment pathway between deployed and stowed shapes, incorporation of a compliant Joule-heating that withstands folding/deployment along with many other factors. Here we present a computational design approach that directly outputs the machine instructions for part fabrication of eSMPCs in the shape of spirals for compact wrap-folding. In the context of deployable antenna reflector, the computational approach allows systematic exploration of varying each spiral petal’s curvature against predictions of its wrap-packaging efficiency, as guided by a parametric design model and computer simulation tool. The computational design process represents a new computer-aided design strategy with eSMPCs, where parametric models coupled with simulations results can inform the geometry of fabricated to ensure applicability of their deployment behavior within context of the application.